Selection of Carbon and Nitrogen Source for 8-Hydroxy 9, 12-Octadecadienoic Acid Production using Endophytic Fungi Curvularia lunata BioMCC FE-00283 - ERWAHYUNI ENDANG PRABANDARI; TUN TEDJA IRAWADI; WAHONO SUMARYONO; KHASWAR SYAMSU (Indonesian Society for microbiology, 2011)
Hydroxyoctadecadienoic acid (HODE) is one of hydroxy fatty acids that has anticancer activity. HODE was previously produced by chemical synthesis or bioconversion from linoleic acid. This is the first paper reported production of HODE by Curvularia lunata an endophytic fungi of Cibotium barometz. Various carbon and hydrogen sources have been tested for their effects on the production of HODE by C. lunata. Glucose, lactose, maltose, xylose, and sucrose were used as carbon sources, while yeast extract, monosodium glutamate, urea, and NH4Cl were used as nitrogen sources. Fermentation was done using 100 ml medium in 250 ml Erlenmeyer flask at 150 rpm, 28 oC for 10 days. HODE products were analyzed by high pressure liquid chromatography using C18 coloumn and eluted by gradient system of acetonitril-water from 15% to 100%. Glucose and monosodium glutamate were found to be the best carbon and nitrogen source. The optimum concentration of glucose and monosodium glutamate for the production of HODE were 10 mg L-1 and 12 mg L-1 respectively.